A multi-base harmonic balance method applied to Hodgkin-Huxley model - Aymen Balti; Valentina Lanza; Moulay Aziz-Alaoui (Mathematical Biosciences and Engineering)
Our aim is to propose a new robust and manageable technique, called multi-base harmonic balance method, to detect and characterize the periodic solutions of a nonlinear dynamical system. Our case test is the Hodgkin-Huxley model, one of the most realistic neuronal models in literature. This system, depending on the value of the external stimuli current, exhibits periodic solutions, both stable and unstable.